2006
DOI: 10.1590/s0102-33062006000400004
|View full text |Cite
|
Sign up to set email alerts
|

Chonecolea doellingeri (Chonecoleaceae, Hepaticae), taxonomia e distribuição geográfica no Brasil

Abstract: RESUMO -(Chonecolea doellingeri (Chonecoleaceae, Hepaticae), taxonomia e distribuição geográfica no Brasil). Chonecolea doellingeri (Nees) Grolle é uma espécie urbanizada que cresce, preferencialmente, sobre estipe de palmeira ou outras árvores. Sua distribuição geográfica foi ampliada para o estado do Mato Grosso do Sul e, também, para municípios de outros estados já referidos. Algumas associações da espécie com outras briófitas são apresentadas. Dados palinológicos, baseados em observações sob microscopia de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
1
7
0
1
Order By: Relevance
“…Analyses made under TEM revealed that the exine is divided into the nexine, an inner layer, and the sexine, an outer layer. Similar exine configurations have been observed for spores of both mosses and liverworts (Heckman 1970;Steinkamp & Doyle 1979;Brown & Lemmon 1988;Estébanez et al 1997;Yano & Luizi-Ponzo 2006;Rocha et al 2008;Caldeira et al 2013;Brown et al 2015;Silva-e-Costa 2015;Rodrigues & Luizi-Ponzo 2015).…”
Section: Sporoderm Structure and Surface Ornamentationsupporting
confidence: 70%
See 2 more Smart Citations
“…Analyses made under TEM revealed that the exine is divided into the nexine, an inner layer, and the sexine, an outer layer. Similar exine configurations have been observed for spores of both mosses and liverworts (Heckman 1970;Steinkamp & Doyle 1979;Brown & Lemmon 1988;Estébanez et al 1997;Yano & Luizi-Ponzo 2006;Rocha et al 2008;Caldeira et al 2013;Brown et al 2015;Silva-e-Costa 2015;Rodrigues & Luizi-Ponzo 2015).…”
Section: Sporoderm Structure and Surface Ornamentationsupporting
confidence: 70%
“…Spore size is a variable characteristic among liverworts. For example, spores of Chonecolea doelligeri (Chonecoleaceae) measured 16.00 µm in polar view (Yano & Luizi-Ponzo 2006), while species belonging to Frullaniaceae (Zhao et al 2011), Dumortieraceae (Yano & Luizi-Ponzo 2011), Porellaceae (Zhao et al 2011), and Ricciaceae (Steinkamp & Doyle 1979;Zhao et al 2011), varied widely from 31 µm (medium-sized) to 127 µm (giant).…”
Section: Spore Size In Plagiochilamentioning
confidence: 99%
See 1 more Smart Citation
“…Ocorre geralmente sobre troncos e, ocasionalmente, pode ser encontrada sobre rocha (Yano et al 2003). É comum sobre estipe ou base de palmeiras em praças, jardins botânicos ou bosques (Yano & Luizi-Ponzo 2006).…”
Section: Drepanolejeunea Araucariaeunclassified
“…Spore morphology and ontogeny are important for evaluating bryophytes taxonomy and phylogeny, as evidenced by several studies (Clarke 1979;Horton 1982;Mishler & Churchill 1984;Blackmore & Barnes 1987;Brown & Lemmon 1980;1984a;b;1988;1991;Estébanez et al 1997;Luizi-Ponzo et al 1997;Caldeira et al 2006;Luizi-Ponzo & Melhem 2006a;b;Yano & Luizi-Ponzo 2006;2011;Savaroglu et al 2007;Rocha et al 2008;Savaroglu & Erkara 2008;Alfayate et al 2013;Brown et al 2015;Rodrigues & Luizi-Ponzo 2015;Savaroglu 2015;Savaroglu et al 2017;Silva-e-Costa et al 2017). Nonetheless, data are still scarce for Erpodiaceae (Erdtman 1965), or have been reported in taxonomic studies (Pursell 1966;1994;Crum 1972;Yano 1984;Yano & Santos 1993;Stone 1997;Pursell & Allen 2002;Daniels et al 2012).…”
Section: Introductionmentioning
confidence: 99%